FINNISH AND SWEDISH NATO MEMBERSHIP – A PATH TOWARDS MORE REGIONAL SECURITY OR INSTABILITY? - Filipović, Aleksa (Serbian political thought, 2024)
The escalation of the Ukrainian crisis at the beginning of 2022 caused a significant change in the European security architecture, and at the same time marked a clear division between the so-called "collective West" and Russia. What became a "proxy war" between Washington, as the leader of the NATO military alliance, and Moscow on the territory of Ukraine, resulted in major geopolitical changes in the northern regions of Europe, such as Scandinavia. Countries previously considered militarily neutral, such as Finland and Sweden, have increasingly begun to align their foreign and security policies with Washington’s interests, leading to their open request to join NATO in May 2022. However, it would be wrong to assume that this was not an expected move on their part, considering that both Finland and Sweden have almost completely integrated into the NATO military and logistics structure, starting from their membership in "NORDEFCO" , to participation in NATO’s regional military exercises. And while Finland became NATO’s 31st member in April 2023, as of the first half of 2023, Sweden’s NATO membership has still not been approved by Turkey and Hungary, although it could be expected for Sweden to become a NATO member in the near future. The aim of this research is to identify potential points of conflict between NATO and Russia that may develop after both Finland and Sweden become NATO members, as well as to assess the possibility of military escalation between Russia and NATO. This will be achieved by applying content analysis during the research of reports, strategies and doctrines, as well as by applying the case-study method, which was used as a research method when analyzing specific examples of the interaction between the Nordic countries, NATO, and Russia in the Scandinavian and Baltic Sea regions. With the accession of Finland to NATO and the expected accession of Sweden, the potential for open military conflict between NATO and Russia has increased. Therefore, it is necessary to understand the consequences of further militarization of Northern Europe, both by NATO member countries (including Sweden) and by Russia, because such a development can lead to the realization of the most dangerous scenario imaginable, which is nuclear escalation and the use of tactical nuclear weapons on the battlefield. This research has identified three points of possible future confrontation between NATO and Russia - the potential of which increases with the membership of Finland and the future membership of Sweden in NATO. The identified points are the Kaliningrad region and the Baltic Sea region, the Russian-Finnish border and the Arctic region. The Kaliningrad region and the Baltic Sea region have already seen an increase in tensions between Russia and NATO member states, such as Poland and the Baltic states. This was particularly evident during the economic blockade of Kaliningrad in 2022, which almost led to Russian military intervention before the dispute was somewhat peacefully resolved. However, Swedish military activities in the region, starting with the militarization of the island of Gotland and its participation in massive annual military exercises under the leadership of NATO, such as Aurora, only lead to greater mistrust and increased tensions between the Nordic countries and Moscow. The Russo-Finnish border, demilitarized since the end of the Cold War, is now being actively fortified from the side of Helsinki, with the recent announcement that Finland will allow United States troops and bases to be stationed in the country. This, in turn, prompted Moscow to announce the formation of new army corps to be stationed along the border, while also deploying a significant number of anti-aircraft systems in the region. In the Arctic region, there has long been a geostrategic rivalry between the US and its allies such as the Nordic countries on the one hand, and Russia and China on the other. Washington can count on a unified security space with Finland and Sweden as NATO members, as well as on the use of significant military and logistical resources that these countries possess when limiting the Arctic ambitions of both Russia and China. This all leads to increased tensions in this region, and a possible future military escalation to control the Northern Sea Route and Arctic resources that are becoming available due to climate change. Taking all of the above into account, it can be concluded that, first of all, the requests of Finland and Sweden for membership in NATO, and then the entry of Finland into NATO, as well as the expected future membership of Sweden in this military alliance led by the United States of America, are the cause of the increase in conflict potential in the region, which in itself can lead to a military escalation between NATO and Russia, and thus to the possible use of tactical nuclear weapons.